Soft-sediment deformation structures in cave deposits and their possible causes (Kalacka Cave, Tatra Mts., Poland). (November 2020) - Szczygieł, Jacek; Wróblewski, Wojciech; Mendecki, Maciej Jan; Hercman, Helena; Bosák, Pavel
Abstract: Clastic deposits in Kalacka Cave in the Tatra Mts. Show soft-sediment deformation structures (SSDS) rare for a cave environments. The poorly sorted allochthonous sediments were deposited within a cave sump under a fluvial regime, likely due to glacially initiated back-flooding during the Last Glacial. The structures include small-scale faults (normal and reverse), folds (upright symmetric anticlines, low-amplitude open folds, W-vergent folds and fault-propagation folds), and water-escape structures. A laboratory experiment is used to assess the possibile liquefaction of a thin soft-sediment filling in a limestone tube, including calculation of the site effects of resonance frequency and amplification coefficient and the site vulnerability index K g . The calculations indicate that seismic waves can be amplified up to 10 times and the expected resonance frequency is 17.05 Hz. We argue that the observed SSDS formed in two stages. First, brittle and ductile deformation structures developed due to gravity-induced slumping. Next, liquefaction produced water-escape structures. The studied SSDS were likely seismically triggered. Favorable conditions occurred during the withdrawal of the last glacier (MIS 2) when the sediments were oversaturated and the Tatra Mts. experienced a strong earthquake (M7.0). Alternatively, high-frequency microearthquakes could have been triggered by slope failure cutting into Kalacka Cave. Highlights: The clastic sediments of Kalacka Cave a rare record of SSDS. A first estimation of the site effects and the vulnerability index of cave sediments. The SSDS in Kalacka Cave are likely co-seismic. The optimal time for the SSDS development in the cave was the end of the Last Glaciation.